INTED2021 Proceedings 2021
DOI: 10.21125/inted.2021.2059
|View full text |Cite
|
Sign up to set email alerts
|

Learning Exchange: A Collaborative Work Between Course Units

Abstract: The joint reflection between teachers from different areas, and with different backgrounds, on the strategies to be implemented in some course units, with the aim of building a scenario that fosters learning and, in parallel, allows the development of transversal skills, led to the idealization of a teaching proposal in which, in addition to valuing learning in a real work context, it was intended to promote the exchange of knowledge acquired by the students from different course units.The proposal in question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In this context, Bachelor's students were assigned the role of performing communication sessions to clarify some of the mechanical processes observed in the companies. Similarly, the CTeSP students were responsible for sharing the hazards and risks inherent to the real work context in the visited companies and for raising awareness about the means of protection to be used [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Bachelor's students were assigned the role of performing communication sessions to clarify some of the mechanical processes observed in the companies. Similarly, the CTeSP students were responsible for sharing the hazards and risks inherent to the real work context in the visited companies and for raising awareness about the means of protection to be used [8].…”
Section: Methodsmentioning
confidence: 99%
“…This approach was followed in the classes of the Safety and Environment CU of the Chemical and Biological Analysis (CBAnalysis) and Mechanical Technology and Vehicles (MTVehicles) CTeSPs of a higher education Institution in the North of Portugal, between the academic years 2016/17 and 2020/21. Based on the experiences carried out in the mentioned CU, Silva, Barros, and Ribeiro [5][6][7][8][9] concluded that when learning with a strong connection to practice is promoted, either in a laboratory or business context, there is evidence of a positive impact on student's motivation and learning. In this way, this paper aims to explain the approach applied in different academic years, reflecting on their advantages/disadvantages and possible perspectives of adaptation to the other component of the CU (Environment) or other courses.…”
Section: Introductionmentioning
confidence: 99%
“…Not only are students' agents of their own transformation, but also higher education institutions and teachers have a fundamental role in mediating these processes, facilitating and moderating learning contexts that are intended to be in constant evolution, transmutation, and transformation. It should be noted that the collaboration between teachers from different areas and with different backgrounds, who have been working as a team for some time [3], [4], [5], [6], [7], [8], [9], has contributed to the debate on teaching and assessment practices, leading to the implementation of some more student-centred practices, with results considered favourable from a motivational and learning point of view. For example, Silva, Barros, and Ribeiro [3], [4], [8], [9] concluded, based on their experiences with CTeSP students, that learning is promoted with a strong connection to practice, namely in the laboratory context, there is evidence of a positive impact on students learning.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the collaboration between teachers from different areas and with different backgrounds, who have been working as a team for some time [3], [4], [5], [6], [7], [8], [9], has contributed to the debate on teaching and assessment practices, leading to the implementation of some more student-centred practices, with results considered favourable from a motivational and learning point of view. For example, Silva, Barros, and Ribeiro [3], [4], [8], [9] concluded, based on their experiences with CTeSP students, that learning is promoted with a strong connection to practice, namely in the laboratory context, there is evidence of a positive impact on students learning. They also verified that the knowledge acquired in the performance of tasks can be useful for other course units.…”
Section: Introductionmentioning
confidence: 99%
“…In order to contribute to the development of some of these skills, and based on teaching experiences already carried out by the authors with course units related to manufacturing processes [9], [10], [11], within the scope of the Manufacturing Processes course unit (UC) of the Master's Degree in Industrial Engineering, from a higher education institution in the north of Portugal, it was proposed to the students to carry out a group work which, in addition to the laboratory component, involved the writing of a scientific article in English and the peer review. As reported by Azevedo, Castro & Gadelha [12], collaborative learning techniques, such as peer review, provide students with the opportunity to exchange experiences that can help them achieve better results, developing critical and self-critical skills during learning.…”
Section: Introductionmentioning
confidence: 99%